Acute metabolic, hormonal and psychological responses to cycling with superimposed electromyostimulation - Wahl, P.; Hein, M.; Achtzehn, S.; Bloch, W.; Mester, J. (European Journal of Applied Physiology, 2014)
Purpose The purpose of the present study was to evaluate the effects of superimposed electromyostimulation (E) during cycling on the acute hormonal and metabolic response, as E might be a useful tool to intensify endurance training without performing high external workloads. Methods Thirteen subjects participated in three experimental trials each lasting 60 min in a randomized order. (1) Cycling (C), (2) cycling with superimposed E (C + E) and (3) E. Human growth hormone (hGH), testosterone and cortisol were determined before (pre) and 0', 30', 60', 240' and 24 h after each intervention. Metabolic stimuli and perturbations were characterized by lactate and blood gas analysis (pH, base excess, bicarbonate, partial pressure of oxygen, partial pressure of carbon dioxide). Furthermore, changes of the person`s perceived physical state were determined. Results C + E caused the highest increases in cortisol and hGH, followed by C and E. Testosterone levels showed no significant differences between C + E and C. Metabolic stress was highest during C + E, followed by C and E. C + E was also the most demanding intervention from an athlete`s point of view. Conclusion As cortisol and hGH are known to react in an intensity dependent manner, the present study showed that superimposed E is a useful method to intensify endurance training, even when performing low to moderate external workloads. Even at lower exercise intensities, additional E may allow one to induce a high (local) stimulus. It can be speculated, that these acute hormonal increases and metabolic perturbations, might play a positive role in optimizing long-term training adaptations, similar to those of intense training protocols.